2020
DOI: 10.1371/journal.pone.0234865
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide-tolerant bacteria isolated from a biopurification system to remove commonly used pesticides to protect water resources

Abstract: In this study, we selected and characterized different pesticide-tolerant bacteria isolated from a biomixture of a biopurification system that had received continuous applications of a pesticides mixture. The amplicon analysis of biomixture reported that the phyla Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria were predominant. Six strains grew in the presence of chlorpyrifos and iprodione. Biochemical characterization showed that all isolates were positive for esterase, acid phosphatase, among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…Both fungi strains were able to remove high concentrations of ATZ, IPR, and CHL, pesticides with different chemical structures and chemical characteristics (Table 1) that confer them several degrees of toxicity and persistence in the environment. The organic biomixture used in BPS is a good source of microorganisms adapted to pesticides, as reported in other studies, including our previous results [12,13,15]. Recently, we reported that bacteria like the Achromobacter sp.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Both fungi strains were able to remove high concentrations of ATZ, IPR, and CHL, pesticides with different chemical structures and chemical characteristics (Table 1) that confer them several degrees of toxicity and persistence in the environment. The organic biomixture used in BPS is a good source of microorganisms adapted to pesticides, as reported in other studies, including our previous results [12,13,15]. Recently, we reported that bacteria like the Achromobacter sp.…”
Section: Discussionsupporting
confidence: 72%
“…Samples were taken and treated according to the description by Briceño et al [12]. The analysis was conducted using a Merck Hitachi L-2130 pump equipped with a Rheodyne 7725 injector and a Merck Hitachi L-2455 diode array detector.…”
Section: Analyses Of Pesticides and Metabolitesmentioning
confidence: 99%
See 3 more Smart Citations